Fibrothorax and Severe Lung Restriction Secondary to Lupus Pleuritis and Its Successful Treatment by Pleurectomy - Sat Sharma; Robert Smith; Fahad Al-Hameed (Canadian Respiratory Journal)
Pleural disease is a common pulmonary manifestation of systemic lupus erythematosus (SLE) that usually responds to corticosteroids and other immunosuppressive agents. In the present report, a new approach, pleural decortication, was used in a patient with medically refractory chronic pleuritis secondary to severe SLE. A 26-year-old woman with known SLE developed progressive dyspnea and pleuritic chest pain over several months. The other systemic manifestations of her lupus were controlled with cyclophosphamide and prednisone. A computed tomography scan revealed a persistent, small, loculated right pleural effusion; pleural thickening; and atelectasis of the right middle and lower lobes. Pulmonary function tests showed a severe restrictive defect. The patient was disabled by her severe dyspnea despite maximal medical therapy, and, therefore, surgery was considered. A right thoracotomy revealed entrapment of the right lung by dense visceral pleura. Decortication was performed. On pathology, pleuritis with vascular pleural adhesions was found. No lupus pneumonitis was noted. Postoperatively, a significant clinical improvement in dyspnea was evident within several weeks. On a 6 min walk test, the patient achieved 384 m with a Borg dyspnea scale rating of 2 compared with 220 m and a Borg dyspnea scale rating of 4 preoperatively. Her forced vital capacity improved from 24% predicted to 47% predicted, and her total lung capacity improved from 35% predicted to 54% predicted. Medical therapy of systemic lupus erythematosus has been proven to be effective in controlling pleuritis in most cases. However, in the event of refractory pleuritis or pleural thickening, decortication may be a viable alternative.